APLIKASI METODE ELEMEN HINGGA GALERKIN PADA PERSAMAAN PANAS DIMENSI SATU - , ASNAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Galerkin Finite Elemen Method (FEM) is one of numerical methods that can be used for finding the approximate solution of differential equation. In this study, the Galerkin Finite Element Method was used for solving two cases: (1) one-dimensional steady state heat equation